Enhancing the activity of metal-organic nanosheets for oxygen evolution reaction by substituent effects - Pang, Wei; Shao, Bing; Chen, Xin; Gu, Quan-Xue; Yang, Fu-Jie; Li, Shixiong; Huang, Jin (Journal of colloid and interface science, 2022)
[Display omitted] •Manufacturing isostructural metal-organic nanosheets possess different ligands group.•The different ligands group of MOFs accurately regulates the electron conductivity, thus further regulating the OER activity.•The as-synthesized metal-organic nanosheets exhibits ultra-high OER activity, comparable to commercial RuO2. Rational designing and synthesizing highly efficient oxygen evolution reaction (OER) electrocatalyst plays a key role in energy conversion. However, due to the numerous factors affecting the activity of electrocatalysis, the understanding of their catalytic mechanism is insufficient, and challenges still exist. Herein, the organic group of the metal-organic nanosheets electrocatalyst was replaced by NH2 to CH3 to controllable regulate the catalytic performance of OER, corresponding to the overpotential of OER reducing from 385 mV to 318 mV at 10 mA cm−2, superior to the commercial precious metal based catalyst RuO2. Furthermore, combining the density functional theory (DFT) and electron localization function (ELF) indicates that the type of ligands group can indirectly modulate the electronic structure of metal catalytic center and the degree of electronic localization of the metal-organic nanosheets catalysts, resulting in the change in electrocatalytic activity. This simple catalytic model is more favorable to investigate the catalytic mechanism, providing a new strategy for the development of efficient electrocatalyst.